Strategic Management of Brazilian Universities - Yahn de Andrade, Cibele; Rus Perez, José Roberto (International Higher Education, 2011)
In order to respond quickly and effectively to the urgency of increasing participation and improving overall quality, strategic planning is key to improvements in Brazilian higher education. Aiming to stimulate the development of a planning culture, in 2001 the federal government began to require that all higher education institutions prepare an Institutional Development Plan (PDI) in order to get approval for their courses and credentials. Yet there is no single formula applicable to Brazil given the diversity of the sector and the different goals and challenges of public and private institutions.